Formative sociology and ethico‐political imaginaries: opening up transnational responses to Palestine–Israel. Issue 4 (17th October 2016) - Sheldon, Ruth
Abstract: Recent contributors to this journal have sought to radicalize sociology by exploring how the discipline might expand political imaginaries and take up non‐reductionist notions of everyday ethics. In a related move, sociologists are exploring the performative potential of sociological practices and sensibilities, while anthropologists are reframing the relationship of ethnography to theory. This article contributes to these projects by focusing on an acute case in which an expanded political imaginary is urgently needed; the tensions between political solidarity and ethical violence in transnational communications around Palestine–Israel. Drawing on an ethnographic study of conflicting activist groups in Britain, I highlight a profound ethical problem: that claims for justice appear to entail a violent refusal to acknowledge 'the other'. The article examines how the dualistic logics structuring sociological imaginaries have occluded and reproduced this impasse, and focuses on an attempt by activists to create non‐violent modes of solidarity. Articulating a role for ethnography in opening up this alternative, I show how responsive and creative sociological methods can bring new languages, imaginaries and political formations into being.